Middle Campanian ammonites and inoceramids from the Wolfe City Sand in northeastern Texas - Cobban, W; Kennedy, W; Kennedy, W (1993)
The middle Campanian Wolfe City Sand in northeastern Texas yields a distinctive ammonite and inoceramid fauna. Four species allow a direct correlation with the Baculites mclearni zone of the Western Interior of the United States. The base of this zone has been dated at 79.9±3.2/79.2±1.6 Ma on the basis of K/Ar determinations on biotite from a bentonite. Inoceramus azerbaidjanensis is also known from the Campanian of the USSR in Azerbaidjan (where the species was first described), western Turkemenia, Georgia, the northern Caucasus, the Crimea, and Donbass. -from Authors